Electromagnetic wave propagation through composite building materials in urban environments at mid‐band 5G frequencies - Ng, Sean Jake Peng (2022)
In an urban built city environment, the performance of electromagnetic (EM) wave propagation through building materials poses a new set of challenges to radio frequency engineers in the prediction of the 5G-network coverage planning. We propose the prospects on the use of composite building materials enhanced with different volumetric fractions of iron (III) oxide (Fe2O3) inclusions as a reddish-brown colouring admixture in modern-day concrete. Using a non-destructive microwave measurement technique, a two-factor 6 × 10 factorial experiment and a randomized controlled statistical study from 3.40 to 3.60 GHz is conducted on 15-cm thick building material prototypes enhanced with 2-wt% to 10-wt% micro-sized Fe2O3 inclusions to evaluate their efficacy on EM wave propagation. Transmission coefficients (S21) data are analysed statistically between treatment and control groups, yielding up to 2.28 dB mean S21 improvement in performance and a fractional bandwidth of 100% by the 2-wt% Fe2O3 treatment group. Electromagnetic characterisations of the fabricated mortar samples with different Fe2O3 inclusions are performed using Nicholson-Ross-Weir model followed by the evaluation of dielectric and propagation losses. Our findings support the use of 2-wt% Fe2O3 as the optimal volumetric fraction which improves the microwave transparency, thus creating potential EM benefits for the fifth-generation (5G) wireless communication systems.